2008
DOI: 10.1016/j.jvs.2008.03.064
|View full text |Cite
|
Sign up to set email alerts
|

A randomized, placebo-controlled trial of doxycycline after endoluminal aneurysm repair

Abstract: Background The late durability of endovascular aneurysm repair (EVAR) has been limited by progressive aortic degeneration believed to be mediated by matrix metalloproteases (MMP). The goal of this study was to evaluate the effect of a MMP inhibitor, doxycycline, on EVAR. Methods and Results Patients undergoing EVAR were randomized to doxycycline (100mg twice daily) or placebo for 6 months following the procedure. Clinical data, blood samples and CT scans were obtained pre-operatively, post-operatively (blood… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
49
1

Year Published

2009
2009
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 56 publications
(52 citation statements)
references
References 26 publications
2
49
1
Order By: Relevance
“…In addition, inhibition of one specific MMP did not provide beneficial outcomes in limiting AAA progression, whereas inhibition of a number of ECM-targeting MMPs was a more effective approach. Consistent with our findings, doxycycline, a broad spectrum MMP inhibitor, has been a promising treatment in preventing AAA expansion and rupture (62)(63)(64)(65), whereas other treatments including ␤-blockers, angiotensin-converting enzyme inhibitors, and statins have been ineffective (1-4, 6). Overall, our study provides evidence that TIMP3 is critical in constructive vascular remodeling, and as such, targeted overexpression of TIMP3 could serve as a promising therapeutic approach in preventing aneurysm formation or controlling its expansion.…”
Section: Discussionsupporting
confidence: 88%
“…In addition, inhibition of one specific MMP did not provide beneficial outcomes in limiting AAA progression, whereas inhibition of a number of ECM-targeting MMPs was a more effective approach. Consistent with our findings, doxycycline, a broad spectrum MMP inhibitor, has been a promising treatment in preventing AAA expansion and rupture (62)(63)(64)(65), whereas other treatments including ␤-blockers, angiotensin-converting enzyme inhibitors, and statins have been ineffective (1-4, 6). Overall, our study provides evidence that TIMP3 is critical in constructive vascular remodeling, and as such, targeted overexpression of TIMP3 could serve as a promising therapeutic approach in preventing aneurysm formation or controlling its expansion.…”
Section: Discussionsupporting
confidence: 88%
“…Furthermore, doxycycline therapy with 100 mg twice daily up to 2 years decreased hemorrhagic risk in brain vascular malformations (Frenzel et al, 2008). Doxycyclin therapy with the same dosage reduced aortic neck dilatation 6 months after endovascular aneurysm repair (Hackmann et al, 2008). Clinical trials with other indications of doxycycline are on the way.…”
Section: Discussionmentioning
confidence: 99%
“…Hackmann et al [24] has showed that the use of doxycycline after EVAR produced a significantly greater decrease in plasma MMP-9 levels and accelerated aneurysmal shrinkage as compared with a placebo. Doxycycline treatment significantly improved the aneurysmal shrinkage rate compared with placebo treated patients at postoperative 6 months ( -13.3%±3.3% vs -3.8%±3.0%, P<0.05).…”
Section: Figmentioning
confidence: 99%